Realizing Healthy and Fit Elderly Through Njangkah Exercise and Simbah Bugar Application - Komalasari, Dwi Rosella; Kurniahadi, Tsania Haifa’; Fadhilla, Fahra; Hanafi, Muhammad Isa; Zain, Siti Azzura; Minalloh, Aldin Nasrun (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2025)
“Seger Waras,” which means healthy and fit, referred to important aspects of well-being for the elderly, including those at the Melati Bendosari Elderly Posyandu, in supporting their functional independence. Due to degenerative factors, the elderly were at risk of declining health and fitness, which could interfere with their daily functional activities. To address this, the Pondok Simbah program was developed. It consisted of the Simbah Pinter, Simbah Njangkah, and Simbah Seger components and involved Posyandu cadres, elderly participants, and their families. The program aimed to improve the knowledge of cadres, the elderly, and their families regarding elderly health and fitness, and to enhance the physical fitness of the elderly, measured using the Six-Minute Walk Test (6MWT). The program included the development of the Simbah Njangkah mobile application, which was made available on the Play Store to support the 5000-step daily exercise routine for the elderly. The program ran for approximately two months and began with Simbah Pinter, a counseling session on health and fitness for cadres, elderly participants, and their families, including training on how to use the application. This was followed by weekly monitoring and evaluation of the 5000-step exercise. After the counseling sessions, there was an increase in knowledge about elderly health and fitness among participants. In addition, elderly fitness levels improved, as shown by a 68 percent increase in the number of individuals who achieved high fitness scores on the 6MWT. The Pondok Simbah program proved to be highly beneficial in improving the health and fitness of the elderly at the Melati Bendosari Elderly Posyandu.